PERAN KEPUASAN KERJA MEMEDIASI PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA PEGAWAI - Dewa Nyoman Benni Kusyana; Luh Nik Oktarini (Juremi: Jurnal Riset Ekonomi, 2024)
This study was carried out to explore how total quality management enhances employee performance by utilizing job satisfaction as an intermediary factor. This study focuses on 35 contract workers within the Student Transport Sector of the Gianyar Regency Transportation Service, using census methods. The process of data gathering using a questionnaire that utilized a Likert Scale with five options for respondents to choose from. Path analysis and the Sobel test are utilized to conduct hypothesis testing. The analysis results demonstrate that total quality management positively and significantly impacts employee performance and job satisfaction, and job satisfaction positively and significantly influences employee performance